Uncovering Metalanguage in Grammar Exam and Its Implication on Students' Cognition - Muhammad Dhika Arif Rizqan; Dewi Wardah Mazidatur Rohmah (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
As language scholars, have you heard the word ‘metalanguage’? and how about the effect of using metalanguage? The current study aimed to investigate the categories of metalanguage in grammar exam. A total of 17 master students in TEFL were voluntarily recruited as the subjects. Their exams were analyzed in detail to collect the data. The researchers conducted a qualitative inquiry called content analysis. The result exposed that the students produced two categories of metalanguage namely technical and non-technical metalanguage. Based on its frequency, technical metalanguage was produced much more frequently than non-technical metalanguage. Both categories of metalanguage affected students’ cognition. However, technical metalanguage ‘drained’ their cognition a lot more while they were not aware about it.